1996
DOI: 10.1523/jneurosci.16-17-05382.1996
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Induction of Long-Term Depression and Long-Term Potentiation Reversal during Aging

Abstract: Homosynaptic long-term depression (LTD) and reversal of long-term potentiation (LTP) were examined extracellularly at CA3-CA1 synapses in stratum radiatum of slices from adult (6-9 months) and aged (20-24 months) Fischer 344 rats. Prolonged low-frequency stimulation (LFS) (900 pulses/1 Hz) of the Schaffer collaterals depressed the initial slope of the excitatory postsynaptic potential (EPSP) in aged but not adult rats. LTD at aged synapses was pathway-specific, persistent, and sensitive to the NMDA receptor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
244
5
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(274 citation statements)
references
References 45 publications
20
244
5
1
Order By: Relevance
“…However, chronic recording studies led to the important discovery that LTP in the perforant path projections to the dentate gyrus decays more quickly in the aged brain (Barnes, 1979). Subsequent work with slices identified deficits in the induction and/or expression of LTP in field CA1 (Deupree et al, 1993;Sankar et al, 2000) while others, in agreement with the earlier studies, found no evidence for deficits in that region (Diana et al, 1994;Norris et al, 1996). It now appears that these discrepancies depend on the stimulation patterns used to induce potentiation (Moore et al, 1993;Lanahan et al, 1997;Watabe and O'Dell, 2003) and the extent to which the animals have learning problems (Tombaugh et al, 2002).…”
Section: Plasticity In Old Agementioning
confidence: 69%
“…However, chronic recording studies led to the important discovery that LTP in the perforant path projections to the dentate gyrus decays more quickly in the aged brain (Barnes, 1979). Subsequent work with slices identified deficits in the induction and/or expression of LTP in field CA1 (Deupree et al, 1993;Sankar et al, 2000) while others, in agreement with the earlier studies, found no evidence for deficits in that region (Diana et al, 1994;Norris et al, 1996). It now appears that these discrepancies depend on the stimulation patterns used to induce potentiation (Moore et al, 1993;Lanahan et al, 1997;Watabe and O'Dell, 2003) and the extent to which the animals have learning problems (Tombaugh et al, 2002).…”
Section: Plasticity In Old Agementioning
confidence: 69%
“…Substantial alteration of NMDA-receptor-mediated LTD has also been observed. In one study, NMDA-receptor-dependent LTD was enhanced in aged CA1 [70], whereas another recent study reported a pronounced reduction [69]. These discrepant results might be due to differences in strains of animals or methodological differences.…”
Section: Weakened Synaptic Plasticitymentioning
confidence: 89%
“…Controversy exists on the effects of development and ageing on LTD. During maturation, induction of LTD is increasingly difficult [30±33]. Some authors report, however, a shift towards facilitation of LTD induction at advanced age [34].…”
Section: Discussionmentioning
confidence: 99%
“…This disturbed Ca 2+ homeostasis could be involved in the plasticity deficits observed, as LTP and LTD are calcium-dependent processes and the balance between LTP and LTD induction seems to be modulated by intracellular Ca 2+ concentrations [8,9]. In experimental models for ageing, as well as in models for diabetes, hippocampal synapses show plasticity modifications favouring LTD induction [11,34,44], whereas LTP expression and maintenance is impaired [11,45]. In ageing rats, it was shown that an increase in Ca 2+ influx through L-type voltagedependent Ca 2+ channels can lower the LTD induction threshold [26].…”
Section: Discussionmentioning
confidence: 99%